ApoJ-Glyc, an early marker of myocardial ischaemia, rapidly maps improved myocardial perfusion in STEMI patients undergoing successful primary PCI. (3rd October 2022) - Kaski, J C; Cubedo, J; Lluch, N; Lopez Sendon, J L; Gorog, D A; Avanzas, P; Herrero Puente, P; Sionis, A; Gonzalez Juanatey, J R; Iniguez, A; Cordero Fort, A; Ako, E; et al.
Abstract: Background: Previous studies using experimental models and clinical retrospective samples have pointed to a potential role of glycosylated apolipoprotein J (ApoJ-Glyc) as a marker for the early detection of myocardial ischaemia. Ischaemia induces intracellular accumulation of non-glycosylated ApoJ that mirrors the reduction in ApoJ-Glyc serum levels in patients presenting with ST-segment elevation myocardial infarction (STEMI). Purpose: The EDICA (Early Detection of Myocardial Ischaemia in Suspected Acute Coronary Syndromes by Apo J-Glyc as a Novel Pathologically based Ischaemia Biomarker) clinical trial assessed the performance of ApoJ-Glyc as a biomarker for the early detection of myocardial ischaemia in patients attending the A&E department with chest pain suggestive of acute coronary syndrome. Here, we report the observed changes in ApoJ-Glyc concentration in STEMI patients at baseline and after primary percutaneous coronary intervention (PPCI). Methods: The EDICA trial, a multi-centre (10 sites), international, in vitro diagnostic study, assessed 404 patients attending the A&E department with suspected ACS. Of these, 291 patients had a final diagnosis of "non-ischaemic" event and 113 of "ischaemic" event. The main inclusion criterion was chest pain of suspected cardiac origin. Blood samples were obtained for the simultaneous assessment of high sensitivity-troponin and ApoJ-Glyc on admission (time 0) and at 1h and 3h thereafter. Two different glycosylated variants of ApoJ (ApoJ-GlycA2 and ApoJ-GlycA6) were analyzed with a novel ELISA in serum samples. Of the "ischaemic" patients, 33 had STEMI, of whom 85% underwent PPCI. Results: As expected, in the presence of myocardial ischaemia, time 0 ApoJ-GlycA2 and ApoJ-GlycA6 serum levels decreased by 34% and 48%, respectively in STEMI patients, compared with non-ischaemic patients, i.e. ApoJ-GlycA2 in STEMI: 66 [52–95] μg/ml vs. non-ischaemic: 100 [72–131] μg/ml; P=0.0002; ApoJ-GlycA6 STEMI: 38 [34–67] vs. non-ischaemic: 73 [56–95] μg/ml; P<0.0001. ApoJ-GlycA6 showed a discriminating ability for the presence of STEMI with a 67% sensitivity and a 83% specificity (AUC=0.747, cut-off of 50μg/ml). In STEMI patients in whom PPCI successfully restored TIMI 3 flow, ApoJ-Glyc levels increased rapidly and significantly compared with time 0 levels (ApoJ-GlycA2: P=0.02 and P=0.003 for 1h and 3h; ApoJ-GlycA6: P=0.02 and P=0.002 for 1h and 3h) and compared to patients in whom PPCI was not performed (Table 1). Conclusions: ApoJ-Glyc concentrations are reduced in STEMI patients on admission and increase rapidly after improved perfusion with PPCI, pointing to a potential role of this biomarker in the early detection of reversible ischaemia and the mapping of reversible changes. The mechanisms whereby ApoJ-Glyc levels rapidly and markedly increase after PPCI are speculative at present and deserve further investigation, together with the potential prognostic value of ApoJ-Glyc in this setting. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Commission 2020-EIC-SMEInstrument Phase 2; Spanish Ministry of Science, Innovation and Universities